The Effect of Corporate Governance on Company Shareholder Value - Lidya, Lidya; Christian, Natalis (Transpublika Publisher, 2026)
Backgrounds: Corporate governance mechanisms and firm financial characteristics are key determinants of corporate performance, with profitability proxounded by Return on Equity (ROE). Corporate performance is shaped by a constellation of governance attributes, encompassing board architecture, ownership configuration, the robustness of internal control frameworks, and the firm’s leverage. Objectives: This study examines the effect of corporate governance mechanisms and financial characteristics on profitability. Specifically, it investigates the roles of Non-Compliance Index, Director Share Ownership, Remuneration, Internal Controls, Extra Committees, Board Independence, Board Size, Leverage, and Liquidity in shaping ROE. Methodology: A quantitatively oriented research design was implemented, utilizing archival financial disclosures as secondary data sources. The empirical estimation relied on multiple linear regression performed on a balanced panel dataset encompassing 500 firm-year observations, with classical assumption tests and hypothesis testing ensuring model robustness. Findings: Simultaneously, governance mechanisms and financial characteristics significantly affect ROE. Partially, Director Share Ownership and Board Size positively influence ROE, while Board Independence has a negative effect. Non-Compliance Index, Remuneration, Extra Committees, Leverage, and Liquidity were not significant. Internal Controls could not be analyzed due to lack of data variation. Conclusions: Not all governance mechanisms directly enhance profitability. Excessive board independence may constrain managerial flexibility, while effective board size and managerial ownership can improve performance. Limitations include a low R² and the use of ROE as the sole performance metric. Future studies should explore alternative performance measures and additional governance variables. Findings provide guidance for designing governance structures that promote profitability, investor confidence, and sustainable business practices.